Hubungan Status Paritas Dan Pekerjaan Dengan Kejadian Anemia Pada Ibu Hamil Trimester II Di PKM Purwokerto Selatan, Kabupaten Banyumas - Desi Haryani Aulia; purwati (NERSMID : Jurnal Keperawatan dan Kebidanan, 2022)
Pregnant women with anemia are at risk of causing preeclampsia, antepartum and postpartum hemorrhage, blood transfusions, and postpartum infections. Therefore, it is necessary to look for the causative factors of anemia in pregnant women. Factors that can cause anemia in pregnant women are parity and occupation. This study aims to analyze the relationship between parity and employment status with the incidence of anemia in pregnant women in the second trimester in the Work Area of ​​the South Purwokerto Public Health Center, Banyumas Regency. This type of research is quantitative using a descriptive correlational design. The sample in this study was 37 pregnant women in the second trimester using total sampling technique and data analysis using the chi square test. The results showed that there were 18 respondents with multipara parity (48.6%) and 21 respondents (56.8%). The chi square test found that there was a relationship between parity status (p 0.003), and occupation 0.038 (<0.05) with the incidence of anemia in pregnant women in the second trimester. Conclusion: There is a relationship between parity and employment status with the incidence of anemia in pregnant women in the second trimester